BOUVERET’S SYNDROME – A RARE CAUSE OF INTESTINAL OBSTRUCTION - FERNANDES, Urânia (2023)
This report is about a clinical case of Bouveret’s Syndrome (BS), a gastric outlet obstruction by a gallstone. It is rare and often a delayed diagnosis in elderly women with comorbidities. These factors contribute to a relevant morbidity and mortality, underlying the importance of an adequate and timely treatment. Its inespecific simptoms makes a high clinical suspicion essential. In the presence of Rigler’s triad the plain abdominal X-ray is diagnostic in one third of the cases but the diagnosis is generally made by CT-scan or esophagogastrosduodenoscopy. This one is often attempted first but surgery is almost always needed. Enterolithotomy/gastrotomy can be complemented by cholecystectomy in a one or two-stage surgery. The most definitive surgical procedures should be restricted for patients in the best physiological conditions.